Energy Consumption Performance for Difference Battery Model Capacity Deployed on Design Network Topologies - Yuslinda Wati Mohamad Yusof,; Murizah Kassim,; Muhammad Nuqman Tukiman,; Mohd Nazri Ismail,; Norakmar Arbain Sulaiman, (International Journal of Integrated Engineering, 2025)
This research investigates energy consumption in Internet of Things (IoT) networks, focusing on how different battery capacities impact energy performance. The study is motivated by the need to optimize power usage in IoT devices, which often rely on limited battery power and can experience significant energy consumption. The study evaluates the performance of four battery types: 3.7V and 7.4V batteries with capacities of 1500mAh and 3000mAh, respectively using NetSim tools. The simulations were conducted over time periods of 1, 12, and 24 hours, and the number of active nodes varied from 1 to 5. The findings reveal that for a network with 1 active node and a 3.7V 1500mAh battery, the total energy consumption was 1.1117%, 13.3438%, and 26.6879% for the durations of 1, 12, and 24 hours, respectively. In contrast, using a 3.7V 3000mAh battery reduced consumption to 0.5553%, 6.6652%, and 13.3306%. These results provide valuable insights into battery deployment strategies for energy-efficient IoT networks, highlighting the importance of selecting appropriate battery models based on network topology and node activity.